Caribbean Report 23-03-1993 - Ransome, Debbie (anchor); Alleyne, Brian (interviewee); Carrington, Edwin (interviewee); Foulkes, George (interviewee); Fraser, Tony (correspondent); Huggins, Russell (interviewee); Seaga, Edward (interviewee); Bhola, Ronnie (correspondent); Klepak, Hal (interviewee); Alleyne, Gary (correspondent) (The British Broadcasting Corporation, 1993)
Cuba is likely to be one of the newest members of a new Association of Caribbean States. In an interview with correspondent Debbie Ransome, host Dominica’s Foreign Minister Brian Alleyne and Dr. Edwin Carrington – CARICOM Secretary General states how this relationship with Cuba and CARICOM would fit into CARICOM’s new plans without causing any controversy with the United States. Britain’s Cuba Solidarity campaign is using the devastation caused in Cuba as another attempt to push Havana up the UK’s Foreign Affairs agenda. The campaign group which includes MPs and Senior Trade Unionists issued an appeal letter to Britain’s Guardian newspaper for financial aid for Cuba. The letter also criticized the way the media attention had focused on Cuba during the recent election but failed to deal with the devastation of the storm. Correspondent Debbie Ransome interviews George Foulkes, British Opposition MP - one of the signatories of the appeal letter, to find out what the group expected to achieve and how far they plan to take their lobbying. Scotland Yard investigation into alleged corruption in the Trinidad and Tobago Police force has led to six counts of charges of corruption being led against a senior Superintendent - Seegram Bagwandeen. He claimed to have been framed and national Security Minister Russell Huggins said that there was no evidence fond of a drug cartel. Correspondent Tony Fraser reports. A Radio advertisement for Jamaica’s two major parties – the People’s National Party and the Jamaica Labour Party is issued to promote the two parties. Opposition Leader - Edward Seaga makes a political statement and correspondent Gary Alleyene gives commentary on the election climate in Jamaica and the addressing of the main issues by the two respective parties. Recent speculation by several British newspapers that Britain may be considering a decision to pull out of its garrison in Belize has been denied by London by spokesmen for both the Ministry of Defense and the Foreign and Commonwealth Office, stating that there are no such plans–correspondent Ronnie Bhola reports from an interview with Professor Hal Klepak of the Royal Military College of Quebec, Canada
Headlines with anchor Debbie Ransome (00:00-00:30).
1. Cuba is likely to be one of the newest members of a new Association of Caribbean States (00:31-05:26).
2. Britain’s Cuba Solidarity campaign is using the devastation caused in Cuba as another attempt to push Havana up the UK’s Foreign Affairs agenda (05:27- 07:43).
3. Scotland Yard investigation into alleged corruption in the Trinidad and Tobago Police force has led to six counts of charges of corruption being led against a senior Superintendent Seegram Bagwandeen (07:44 - 09:26).
Keywords: Association of Caribbean States.; Caribbean Community.; Cuba —Foreign Relations—United States.; Caribbean Area--Politics and government.; Drug traffic--Caribbean Area.; Great Britain.--Metropolitan Police Office. Criminal Investigation Dept.--Trinidad and Tobago.; Police corruption--Trinidad and Tobago.; Police corruption--Caribbean area.; Crime—Trinidad and Tobago.; Jamaica--Politics and government.; Elections—Jamaica.; Political campaigns--Jamaica.; Belize--Politics and government.; Belize--Foreign relations--Great Britain.; Belize--Armed Forces--Great Britain.; Drug traffic—Commerce--Belize.